Miss Scarlet & the duke. Season one [videorecording (DVD)]. - Phillips, Kate (Actor); Martin, Stuart, 1986-; Belton, Cathy (PBS, 2021)
Eliza Scarlet joins forces with a Scotland Yard inspector to solve crime in nineteenth century London.